Carthamin yellow-loaded glycyrrhetinic acid liposomes alleviate interstitial fibrosis in diabetic nephropathy - Yifei Wang; Wenfang He; Peiyao Ren; Li Zhao; Danna Zheng; Juan Jin (Renal Failure)
Objectives To investigate the therapeutic efficacy of Carthamin yellow (CY)-loaded glycyrrhetinic acid (GA) liposomes in treating diabetic nephropathy (DN), particularly in alleviating renal interstitial fibrosis and improving kidney function.Methods CY-loaded GA liposomes were prepared and characterized for structural stability and controlled release. DN rat models were treated with CY-loaded GA liposomes, and kidney pathology, function, collagen deposition, and TGF-β1 expression were evaluated. The effects of CY-loaded GA liposomes were compared to Vitamin E and CY alone. In vitro experiments with TGF-β1-stimulated human renal interstitial fibroblasts (hRIFs) examined the effects of CY-loaded GA liposomes on cell proliferation and the expression of fibrotic markers. Mechanistic studies assessed the role of the TGFBR1/Smad2/Smad3 pathway using TGFBR1 overexpression experiments.Results The CY-loaded GA liposomes exhibited a stable structure and controlled release profile. In DN rats, treatment with CY-loaded GA liposomes significantly alleviated kidney damage, improved kidney function, reduced collagen deposition and fibrosis, and downregulated TGF-β1 expression, showing superior effects compared to Vitamin E or CY alone. In TGF-β1-stimulated hRIFs, CY-loaded GA liposomes effectively suppressed cell proliferation and reduced the expression of Cyclin D1, PCNA, fibronectin, and collagen I. The inhibitory effects were stronger than CY alone and were mediated by the inactivation of the TGFBR1/Smad2/Smad3 pathway, as confirmed by TGFBR1 overexpression studies.Conclusions CY-loaded GA liposomes demonstrated significant therapeutic efficacy in alleviating renal interstitial fibrosis in DN by targeting the TGFBR1/Smad2/Smad3 pathway. This novel drug delivery system provides a promising approach for the treatment of DN.